2008
DOI: 10.3938/jkps.53.461
|View full text |Cite
|
Sign up to set email alerts
|

Local Structural Properties of ZnO Nanoparticles, Nanorods and Powder Studied by Extended X-ray Absorption Fine Structure

Abstract: We investigated the local structural properties of ZnO nanoparticles (NPs), nanorods and powder by using extended X-ray absorption ne structure (EXAFS). The average diameter and size of the ZnO NPs and nanorods were about 4.5 nm and 40 nm, respectively. The EXAFS analysis revealed that the bonding lengths of atoms in the ZnO nanorods were slightly elongated along the c-axis while they were shrunken in the ab-plane, as compared with those of the ZnO powder. We did not observe a vacancy or an extra disorder for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
2
7
1
Order By: Relevance
“…The accurate determination of the location of dopants is important for the explanation of the dopant effect on the properties of the parental materials (Tsuzuki et al, 2019). While X-ray diffraction (XRD) is the standard method for the determination of the crystallographic structure and phase of bulk materials, doping studies can be challenging for XRD when submicrometre-size particles are to be investigated (Jeong et al, 2008). For study of the electronic structure, local order and conformation of the dopant ion B with respect to the host material ZnO, we resort to synchrotron radiation based X-ray absorption spectroscopy (XAS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accurate determination of the location of dopants is important for the explanation of the dopant effect on the properties of the parental materials (Tsuzuki et al, 2019). While X-ray diffraction (XRD) is the standard method for the determination of the crystallographic structure and phase of bulk materials, doping studies can be challenging for XRD when submicrometre-size particles are to be investigated (Jeong et al, 2008). For study of the electronic structure, local order and conformation of the dopant ion B with respect to the host material ZnO, we resort to synchrotron radiation based X-ray absorption spectroscopy (XAS).…”
Section: Introductionmentioning
confidence: 99%
“…For the XAS we consider two parts: near-edge X-ray absorption fine structure (XANES) and extended X-ray absorption fine structure (EXAFS), which are useful techniques to characterize both electronic structure and local structural properties of materials (Braun, 2017;Ankudinov & Rehr, 1997). There are few studies on the local structural properties of ZnO nanoparticles determined via the EXAFS technique, which describes the bonding lengths, bonding length disorders, coordination and atomic species of neighboring atoms around a probe atom (Jeong et al, 2008). Chiou et al (2004a) worked on the electronic structure of ZnO nanorods by angle-dependent X-ray absorption spectroscopy at the oxygen (O) K-edge and zinc (Zn) L 3 -and K-edges.…”
Section: Introductionmentioning
confidence: 99%
“…Both the ZnO-4/FTO and ZnO-4/Si Zn L 3 -edge spectra indicate the presence of wurtzite ZnO structure in that the Zn L 3 -edge peak near 1021.3 eV is associated with strong Zn 2+ signals in ZnO wurtzite structures [36,37]. The local band structures of the ZnO nanorods are expected to be different from those of the bulk ZnO because of the size effect, structural distortion, and disorder, but we have confirmed that both ZnO-4/FTO and ZnO-4/Si have the same wurtzite ZnO nanostructures [38,39].…”
Section: Resultsmentioning
confidence: 61%
“…Both the ZnO-4/FTO and ZnO-4/Si Zn L 3 -edge spectra indicate the presence of wurtzite ZnO structure in that the Zn L 3 -edge peak near 1021.3 eV is associated with strong Zn 2+ signals in ZnO wurtzite structures [ 36 , 37 ]. The local band structures of the ZnO nanorods are expected to be different from those of the bulk ZnO because of the size effect, structural distortion, and disorder, but we have confirmed that both ZnO-4/FTO and ZnO-4/Si have the same wurtzite ZnO nanostructures [ 38 , 39 ].
Fig.
…”
Section: Resultsmentioning
confidence: 71%